SoundCloud Rap: An investigation of community and consumption models of internet practices. Issue 2 (15th March 2022) - Dunham, Ian
ABSTRACT: The technosocial impacts of the internet are the result of a dynamic exchange in which multiple agents compete, cooperate, and coexist for a variety of reasons that stem from just as many motivations. On SoundCloud, a popular music-based social networking platform, this suspense is in full tilt—a few short years ago, it was on the brink of shutdown because of cash shortages, forcing mass layoffs, only to become the site of a burgeoning hip hop community in 2017 and 2018. What has been labeled "SoundCloud Rap" represents a unique social phenomenon that is simultaneously a community, a particular approach to governance, and a network that relies on the symmetrical interplay of humans and machines. Using a theoretical framework grounded in a discussion of the diversity of the internet's formulations, this paper analyzes SoundCloud Rap, concluding that artists and listeners operate under both a community model and a consumption model. An empirical study of data collected from the site for artist and listener data support this discussion. Last, I consider the wave of SoundCloud Rap artists and the novel place within the industry they currently occupy, and whether the subgenre can leave any lasting marks on musical technoculture.